ANALISIS KINERJA ANGGARAN DAN REALISASI ANGGARAN PERUSAHAAN (Studi Kasus Pada UMKM Agen BRILink Putri Cell Jl. Panglima Polim No.1,Poris Tangerang ) - Nababan, Putri Novi Mariana; Sihombing, Elsa Medika K (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2025)
This research aims to analyze spending performance in budget realization reports at BRILink Putri Cell Agent UMKM, with a focus on the effectiveness and efficiency of budget management. The data used covers various spending categories, such as operations, investment, salaries and benefits, maintenance, and marketing. The research results show that the average budget realization reached 99%, reflecting management that was almost in accordance with the planned budget. the investment expenditure category recorded the highest realization, namely 104%, while other categories such as operations, salaries and maintenance had slightly lower realization levels. expenditure to income ratio analysis shows a positive trend, with efficiency increasing over time. In the first quarter of 2024, the operating expenditure to revenue ratio is 40%, which then decreases to 35% in the third and fourth quarters. This efficiency provides more room for companies to invest in strategic development. The cost per unit of production is calculated to measure further efficiency, where operational expenditure contributes the largest cost, namely IDR 95 per unit.  The research results also highlighted that the company's strategic objectives, such as increasing production and developing infrastructure, were almost completely achieved with a high level of effectiveness. These findings show that BRILink Putri Cell Agent UMKM,, are able to manage resources well to support the growth and sustainability of their business.